2013
DOI: 10.1002/cctc.201300775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nature and Location of Copper Species on the Catalytic Nitric Oxide Selective Catalytic Reduction Performance of the Copper/SSZ‐13 Zeolite

Abstract: . (2014). Effect of the nature and location of copper species on catalytic nitric oxide selective catalytic reduction performance of the copper/SSZ-13 zeolite. ChemCatChem, 6(2), 634-639. DOI: 10.1002/cctc.201300775 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…As discussed in Section 2.1.2, there are evidences for the formation of mono-and multi-nuclear Cu(II) species other than Z[Cu(II)OH] under high-temperature oxidative treatment of high-loading Cu-SSZ-13 materials with Si/Al ratio in the 13-20 range. 25,27,29,58,145,146 In this respect, the most sensitive techniques are UV-Vis-NIR and Raman spectroscopy, whereas FTIR in the υ(OH) region can be employed indirectly to track the temperature-dependent dynamics of Z[Cu(II)OH] 27 through its fingerprint band at ca. 3650 cm 1 .…”
Section: Composition Impact On Cu(ii) Species Other Than Z[cu(ii)oh]mentioning
confidence: 99%
“…As discussed in Section 2.1.2, there are evidences for the formation of mono-and multi-nuclear Cu(II) species other than Z[Cu(II)OH] under high-temperature oxidative treatment of high-loading Cu-SSZ-13 materials with Si/Al ratio in the 13-20 range. 25,27,29,58,145,146 In this respect, the most sensitive techniques are UV-Vis-NIR and Raman spectroscopy, whereas FTIR in the υ(OH) region can be employed indirectly to track the temperature-dependent dynamics of Z[Cu(II)OH] 27 through its fingerprint band at ca. 3650 cm 1 .…”
Section: Composition Impact On Cu(ii) Species Other Than Z[cu(ii)oh]mentioning
confidence: 99%
“…63 Furthermore, Guo et al also observed by Raman spectroscopy the formation of Cu-O-Cu dimers upon dehydration of Cu-chabazite. 64 However, since Cu sites seem to be very mobile, 50,61,65 one has to follow their structural dynamics under realistic reaction conditions, i.e. operando.…”
Section: Exafs Of Dehydrated Catalysts Is Presented Inmentioning
confidence: 99%
“…This difference is expected to greatly influence Cu 2+ positioning and Cu 2+ /Cu + redox processes. Besides isolated Cu ions, more recent spectroscopic studies seem to suggest that oxygen-bridged dicopper species (dimers) can also exist in Cu-CHA, especially at high Cu loadings and in the presence of oxygen [32,33]. In any case, it is important to realize that: ) [34].…”
Section: Roles Of Different Cu Species and Nh 3 -Scr Kineticsmentioning
confidence: 99%